Improvement of Methods for Calculating Thermal Characteristics of Loop Air Heaters - Yurko, V.; Ganzha, A.; Tarasenko, O.; Tiutiunyk, L. (Технологічний центр, 2021)
Utilization of heat from gases leaving the waelz process is a promising way to increase its energy efficiency and nvironmental safety. Taking into account the gas dustiness, the most rational is the use of a loop air heater, which is a multi-pass and multi-section heat exchanger with a complex mixed scheme of coolant movement. In modern conditions, when the methods and means of calculation of such devices are simplified, the task of obtaining improved methods and means of calculation, determining the efficiency and reliability of their work is relevant. Two mathematical models of the process of heat transfer and hydroaerodynamics in a multi-pass tubular air heater with a cross-circuit of coolants are used. The developed models for the loop air heater are based on the main methods of thermal calculation: a simpler method of correction factor to the average logarithmic temperature pressure and a discrete P-NTU method, which allows obtaining local thermal characteristics of the surface. Diagrams of distribution of heat transfer coefficients, heat transfer, local temperatures of flue gases, air and pipe walls are constructed. The influence of dust and dust particle size on heat transfer is determined. When the flue gas dust is 50 g/Nm3 and with a dust particle size of 1 μm, the heat transfer coefficient increases by 12 %. The application of the air heater design with different schemes of coolant movement is substantiated. The developed universal methods allow determining the thermal productivity of heat exchangers and obtaining the distribution of local temperature characteristics on the heating surface. It is also possible to identify places of possible overheating of the heat exchange surface and the course of corrosion processes, taking into account the design of recuperators, operating conditions, operating modes and different schemes of coolant movement

Утилізація теплоти газів, які відходять після вельц-процесу, є перспективним напрямом підвищення його енергоефективності та екологічної безпеки. З урахуванням запиленості газів найбільш раціональним є використання петлевого повітронагрівача, який є багатоходовим та багатосекційним теплообмінником зі складною змішаною схемою руху теплоносіїв. В сучасних умовах, коли методи та засоби розрахунків таких апаратів є спрощеними, задача одержання уточнених методів і засобів розрахунків, визначення ефективності та надійності їх роботи є актуальною. Використано дві математичні моделі процесу теплопередачі та гідроаеродинаміки в багатоходовому трубчатому повітронагрівачі з перехресною схемою руху теплоносіїв. Розроблені моделі для петлевого повітронагрівача базуються на основних методах теплового розрахунку: більш простому методі поправкового коефіцієнта до середньологарифмічного температурного напору та дискретному P-NTU-методі, який дозволяє одержати локальні теплові характеристики поверхні. Побудовано діаграми розподілу коефіцієнтів тепловіддачі, теплопередачі, локальних температур димових газів, повітря та стінок труб. Визначено вплив запиленості та розміру пилових частинок на теплопередачу. При запиленості димових газів 50 г/Нм3 і з розміром пилових частинок 1 мкм коефіцієнт теплопередачі зростає на 12 %. Обґрунтовано застосування конструкції повітронагрівача з різними схемами руху теплоносіїв. Розроблені універсальні методи дозволяють визначити теплову продуктивність теплообмінників та одержати розподіл локальних температурних характеристик по поверхні нагріву. Також є можливість виявити місця можливого перегріву поверхні теплообміну та протікання процесів корозії з урахуванням конструкції рекуператорів, умов експлуатації, режимів роботи та різних схем руху теплоносіїв.
Удосконалення методів розрахунку теплових характеристик петлевих повітронагрівачів
Keywords: loop air heater (heat recovery); P-NTU method; correction factor method; discrete (interval) calculation; cross-circuit of coolant motion; energy efficiency; петлевий повітронагрівач (теплоутилізатор); P-NTU-метод; метод поправкового коефіцієнту; дискретний (інтервальний) розрахунок; перехресна схема руху теплоносіїв; енергоефективність